Current-voltage and capacitance-voltage characteristics of Al/p-type silicon/organic semiconductor based on phthalocyanine rectifier contact - Yakuphanoğlu, Fahrettin; Kandaz, M.; Senkal, B. F. (Elsevier Science Sa, 2008)
Electrical characteristics of the Al/p-type silicon/2,9,16,23-tetrakis-{6-(-thiophene-2-carboxylate)-hexylthio} phthalocyaninato cobalt(II) organic semiconductor contact have been investigated by current-voltage and capacitance-voltage measurements. The ideality factor (1.33), barrier height (0.90 eV) and series resistance (314.5 k Omega) of the Al/p-Si/CoPc contact were obtained from current-voltage characteristics. The barrier height obtained for the Al/p-Si/CoPc diode is significantly higher than that of obtained for the conventional Al/p-Si Schottky diode. The CoPc organic layer modifies the effective barrier height of Al/p-Si Schottky diode as the organic film forms a physical barrier between Al metal and the p-Si. The interface-state density of the diode was determined and interface-state density was found to vary from 1.23x 10(14) eV(-1) cm(-2) to 0.69 x 10(14) eV(-1) cm(-2). It is evaluated that the CoPc organic layer modifies electrical parameters and interface properties of Al/p-Si junction. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Organic semiconductor; Metal-organic-inorganic; semiconductor contacts; Interface-state density